Effect of Institutional Case Volume on In-hospital Mortality After Living Donor Liver Transplantation: Analysis of 7073 Cases Between 2007 and 2016 in Korea. Issue 5 (May 2019) - Yoo, Seokha; Jang, Eun Jin; Yi, Nam-Joon; Kim, Ga Hee; Kim, Dal Ho; Lee, Hannah; Jung, Chul-Woo; Ryu, Ho Geol
Abstract : Background: The relationship between institutional case volume and clinical outcomes after living donor liver transplantation is not clarified. Methods: We conducted a nationwide retrospective cohort study using the database of Korean National Healthcare Insurance Service. Between January 2007 and December 2016, 7073 adult living donor liver transplantations were performed at 50 centers in Korea. Centers were categorized according to the average annual number of liver transplantations: >50, 10 to 50, and <10. Results: In-hospital mortality rates in the high-, medium-, and low-volume centers were 2.8%, 4.1%, and 6.7%, respectively. After adjustment, in-hospital mortality was significantly higher in low-volume centers (adjusted odds ratio, 2.287; 95% confidence interval, 1.471-3.557; P < 0.001) and medium-volume centers (adjusted odds ratio, 1.676; 95% confidence interval, 1.089-2.578; P = 0.019) compared with high-volume centers. Long-term survival for up to 9 years was better, and intensive care unit and hospital length of stay were shorter in high-volume centers. Conclusions: Centers with higher case volume (>50 liver transplantations/year) had better outcomes after living donor liver transplantation, including in-hospital mortality and long-term mortality compared with centers with lower case volume (⩽50 liver transplantations/year).